S70 Neonatal airway epithelial cell IL-8 responses to infection are reduced in those who go on to wheeze. (15th November 2016) - Turner, SW; Miller, D; Walsh, G; Power, U; Shields, M; Devereux, G
Abstract : Introduction: Airway epithelial cells (AEC) are important contributors to the innate immune system and AEC function in children with asthma differs to that of children without asthma. We recruited a birth cohort to establish whether AEC function was abnormal before the onset of asthma symptoms. Methods: Pregnant mothers were recruited and nasal AEC brushings were collected from neonates within 48 hours of birth. Cells were cultured in a submerged model and stimulated with tumour necrosis factor alpha/interleukin-1 beta (TNFa/IL1b), lipopolysaccharide (LPS) and house dust mite (HDM). The mediators in the culture supernatant were quantified by cytometric bead array or ELISA and included: interleukin (IL)−6, IL-8, granulocyte macrophage colony stimulating factor (GMCSF) and interferon gamma (IFNg). The primary outcome of interest was IL-8 expressed as median [interquartile range] in pg/mg protein. Parents returned a postal questionnaire when their child was four years old. Results: AEC were successfully cultured in 139 neonates of whom 120 were contacted and 85 questionnaires were returned. The mean age was 3.8 years, 42 were boys and 10 reported wheeze in the previous 12 months. Neonates who had recent wheeze at four years had reduced median AEC IL-8 release after exposure to TNFa/IL1b (60 [33, 71] versus 105 [64, 157], p = 0.002, see Figure 1 ) or to LPS (2.2 [0, 9.0] versus 10.5 [4.6, 24.0] p = 0.038) compared to those who did not wheeze. Neonatal AEC GMCSF release was also reduced after exposure to TNFa/IL1b in those who later wheezed compared to non wheezers (0.09 [0.01, 0.72] versus 0.67 [0.32, 1.48] p = 0.014). Neonatal AEC release of IFNg and IL-6 were not associated with later wheeze. Maternal asthma was not associated with AEC IL-8 release. Conclusions: These results suggest that an abnormality which is present at birth in AEC response to infection is important to asthma causation.